Getting together - Ancona, George (New York : Macmillan/McGraw-Hill School Pub., Comp, 1993)
The people you see are real students and their teachers. Some of the children go to Turquoise Trail Scholl in Santa Fe, New Mexico. Others go to the Carroll Elementary School in Bernallio, New Mexico.
Keywords: School activities